1996
DOI: 10.1302/0301-620x.78b6.0780965
|View full text |Cite
|
Sign up to set email alerts
|

‘Stress’ Distributions Inside Intervertebral Discs

Abstract: We investigated the distribution of compressive 'stress' within cadaver intervertebral discs, using a pressure transducer mounted in a 1.3 mm diameter needle. The needle was pulled along the midsagittal diameter of a lumbar disc with the face of the transducer either vertical or horizontal while the disc was subjected to a constant compressive force. The resulting 'stress profiles' were analysed in order to characterise the distribution of vertical and horizontal compressive stress within each disc. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
172
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(191 citation statements)
references
References 20 publications
14
172
1
4
Order By: Relevance
“…Many reasons are related to the discogenic pain, such as disruption of the nucleus pulposus and anulus fibrosus, ingrowth of the granulation tissue and nerve endings into deeper layer of the annulus [13,14], irritation by inflammatory cytokines [15][16][17], mechanical stimulation associated with lumbar movement on the sinuvertebral nerve ending distributed in the outer one-third of the annulus and posterior longitudinal ligament [18], and epidural inflammation due to annular tears can also contribute to the pathogenesis of pain [19]. Although all mechanisms can exist in each patient, one or two of them maybe dominant in pain generation.…”
Section: Discussionmentioning
confidence: 99%
“…Many reasons are related to the discogenic pain, such as disruption of the nucleus pulposus and anulus fibrosus, ingrowth of the granulation tissue and nerve endings into deeper layer of the annulus [13,14], irritation by inflammatory cytokines [15][16][17], mechanical stimulation associated with lumbar movement on the sinuvertebral nerve ending distributed in the outer one-third of the annulus and posterior longitudinal ligament [18], and epidural inflammation due to annular tears can also contribute to the pathogenesis of pain [19]. Although all mechanisms can exist in each patient, one or two of them maybe dominant in pain generation.…”
Section: Discussionmentioning
confidence: 99%
“…In normal disc, the posterior annulus is weaker than the anterior annulus [9], but sustains higher stresses [10]. Aging and degeneration would compromise disc structure and disturb stress distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Aging and degeneration would compromise disc structure and disturb stress distributions. Adams et al [10] reported that in degenerative disc the compressive stress was reduced 30 % within the central nucleus region, but increased 160 % within the surrounding annulus. In addition, the changes of degeneration were greater on the posterior annulus than the anterior.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleus pressure was raised corresponding to increase in volume by the injection of fluid (Andersson and Schultz 1979;Ranu 1993) and fell when the volume was decreased by either surgical excision (Brinckmann and Grootenboer 1991) or nucleoplasty (Chen et al 2003). There was a reduction in the hydrostatic pressure in the functional nucleus of discs that were subjected to rigorous creep loading; 1-2 kN maintained for 2-3 h (Adams et al 1996). This reduction can be partially explained by an increase in facet loading, especially in lordotic postures.…”
Section: Introductionmentioning
confidence: 99%